MENINGKATKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI (HOTS) SISWA KELAS V PADA MATA PELAJARAN MATEMATIKA MELALUI MODEL PROBLEM POSING DI SDN DURI KOSAMBI 10 PAGI - Haya Difa Nabilah; M. Kurnianti, Endang; Hasanah, Uswatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to enhance students' mathematical Higher-Order Thinking Skills (HOTS) through the implementation of the Problem Posing model. This research employs the Classroom Action Research (CAR) method, adapting the O’Leary model, and was conducted over three cycles. The subjects of this study were 30 fifth-grade students. Data collection was facilitated through HOTS test instruments and classroom observations.The results indicated a progressive improvement in students' high-order thinking abilities. In the pre-research phase, only 5 students (16.67%) achieved the target mastery score. Following Cycle I, this number increased to 13 students (43.33%), and further rose to 22 students (73.33%) in Cycle II. By Cycle III, all 30 students (100%) successfully reached the predetermined minimum proficiency standard of 80%. Based on these outcomes, it can be concluded that the Problem Posing model effectively improves the Higher-Order Thinking Skills (HOTS) of fifth-grade students at SDN Duri Kosambi 10 Pagi.